Photonic Crystal Enhanced Fluorescence: A Review on Design Strategies and Applications - Yanyu Xiong; Skye Shepherd; Joseph Tibbs; Amanda Bacon; Weinan Liu; Lucas D. Akin; Takhmina Ayupova; Seemesh Bhaskar; Brian T. Cunningham (Micromachines, 2023)
Nanoscale fluorescence emitters are efficient for measuring biomolecular interactions, but their utility for applications requiring single-unit observations is constrained by the need for large numerical aperture objectives, fluorescence intermittency, and poor photon collection efficiency resulting from omnidirectional emission. Photonic crystal (PC) structures hold promise to address the aforementioned challenges in fluorescence enhancement. In this review, we provide a broad overview of PCs by explaining their structures, design strategies, fabrication techniques, and sensing principles. Furthermore, we discuss recent applications of PC-enhanced fluorescence-based biosensors incorporated with emerging technologies, including nucleic acids sensing, protein detection, and steroid monitoring. Finally, we discuss current challenges associated with PC-enhanced fluorescence and provide an outlook for fluorescence enhancement with photonic-plasmonics coupling and their promise for point-of-care biosensing as well monitoring analytes of biological and environmental relevance. The review presents the transdisciplinary applications of PCs in the broad arena of fluorescence spectroscopy with broad applications in photo-plasmonics, life science research, materials chemistry, cancer diagnostics, and internet of things.